Local communities’ awareness and use of urban forests in Selangor - A. Manan, Nur Hafzhan (2018)
This study was conducted to examine local communities’ awareness and use of urban forest. In addition, local communities’ awareness towards the existence of urban forest were compared with their demographic background. This study found that more than half (58%) of the respondents were not aware about the existence of nearby forest. However, 42% of respondents who were aware about the forest, knew about the function of forest that is for research, education and extension (61.5%). The study also found that only 69 respondents have been to that forest. Urban forests were mostly used for exercise and enjoy peace and quietness (19%) respectively. Most respondents (25%) spent more than 2 hours in the forest, came during weekend (73.9%) and with friends (78%), most preferred forest features was nature scenery (54%), while the least preferred forest features was group of none (32%). There was a significant difference (P = 0.031) between awareness and education level. Results from this study can be beneficial to forest managers, conservators, city planners and policy makers as to provide guidance on planning the urban forest.